2012
DOI: 10.3174/ajnr.a3147
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of IgG4-Related Disease in the Head and Neck and Brain

Abstract: SUMMARY:IgG4-related disease is characterized by histologic fibrosis with IgG4-positive plasma cell infiltration. Our study evaluated MR imaging features of IgG4-related disease in the head and neck and brain. Images from 15 patients were retrospectively evaluated for the location, signal intensity, and enhancement patterns of lesions. Lacrimal gland enlargement was observed in 8 cases. Other lesions included orbital pseudotumor in 5, pituitary enlargement in 5, and cranial nerve enlargement in 7; the infraorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 20 publications
(25 reference statements)
2
65
0
Order By: Relevance
“…19 Several previous publications regarding IgG4-related disease of the head and neck have focused their attention within the orbit on lacrimal gland enlargement. 4,7,17,18 Although lacrimal gland enlargement was com- mon in this case series, extraocular muscle enlargement was the most common finding. Several authors have also reported the presence of perineural spread of IgG4-related disease, with expansion of the associated neural foramina.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…19 Several previous publications regarding IgG4-related disease of the head and neck have focused their attention within the orbit on lacrimal gland enlargement. 4,7,17,18 Although lacrimal gland enlargement was com- mon in this case series, extraocular muscle enlargement was the most common finding. Several authors have also reported the presence of perineural spread of IgG4-related disease, with expansion of the associated neural foramina.…”
Section: Discussionmentioning
confidence: 59%
“…Several authors have also reported the presence of perineural spread of IgG4-related disease, with expansion of the associated neural foramina. 4,8,9,17,18 Limitations of our study include its retrospective nature. Additionally, the imaging-acquisition parameters were not consistent among all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Parenchymal and structural brain lesions have been described, confirmed by biopsy examination, which showed improvement with glucocorticoids and rituximab. 56 Aside from the impingement of cranial nerves by expanding orbital tumors, the disease can cause hypertrophic pachymeningitis.…”
Section: Central Nervous Systemmentioning
confidence: 96%
“…Imaging findings of IgG4-related disease differ based on involved organ. Imaging of IgG4-related disease in head and neck lesions such as lacrimal gland, orbital mass and pituitary reveals hypointense signal in T 2 of MRI, 47 which was observed in MRI of our second patient. So, the diagnosis of IgG4-related disease should be suggested for T 2 -weighted hypointense enhancing lesions of the head and neck such as lacrimal glands, as in our second patient, and further investigations should be performed.…”
mentioning
confidence: 88%